Evaluación de productos biológicos y químicos, para el control de pythium sp y fusarium sp, en el cultivo de Tomate (lycopersicum esculentum) hibrido f-1 (variedad em9900t y f-1 h y b) sector Quillo Allpa, distrito y provincia de Lamas - Bocanegra Gonzales, Edin (2012)
Among the vegetables, tomato fruits have a wide acceptance and preference for its taste qualities and the possibility of its wide use in state fresh or prepared in various forms, and thus constitutes a major vegetables grown worldwide. There is currently a trend almost widespread constantly seek alternatives to production systems used in the field of agriculture with the laudable aim of raising crop yields and cause an increase in food availability for the growing population of mankind. In the rainy season the incidence of disease is higher while during the dry season pests are the biggest problem. However, such problems can be overcome through a set of agricultural practices including management methods and appropriate controls, which have to be made ​​in when and how exactly indicated, since they depend on the success a good harvest. Reason why in this thesis sought to assess the effect of microorganisms and chemical and biological control of Pythium sp and Fusarium in tomato crop in this area of ​​Lamas.